2018
DOI: 10.1007/978-3-319-77932-4_34
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation for Women

Abstract: Cardiac rehabilitation provides comprehensive secondary prevention services and improves outcomes among patients with coronary heart disease, systolic heart failure, and other cardiac rehabilitation indications. Worldwide, cardiac rehabilitation services are underutilized. Underutilization is more common among women than in men. This chapter reviews barriers to referral, enrollment, and adherence among women and potential interventions to improve women's participation in cardiac rehabilitation. Gender similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 75 publications
0
3
0
1
Order By: Relevance
“…Since the efficacy of GDMT on HFmrEF patients has been controversial and HFmrEF might be perceived by clinicians as a 'less severe' form of HFrEF, the implementation of GDMT might be more likely to be biased by miscellaneous factors such as socioeconomic characteristics 22 or a higher likelihood of adverse effects of GDMT in women than in men. [23][24][25] The efficacy of GDMT on HFmrEF patients has not been established since no randomized controlled trials (RCTs) were conducted exclusively on this population.…”
Section: Sex-related Difference In the Association Of Lower Lvef With...mentioning
confidence: 99%
“…Since the efficacy of GDMT on HFmrEF patients has been controversial and HFmrEF might be perceived by clinicians as a 'less severe' form of HFrEF, the implementation of GDMT might be more likely to be biased by miscellaneous factors such as socioeconomic characteristics 22 or a higher likelihood of adverse effects of GDMT in women than in men. [23][24][25] The efficacy of GDMT on HFmrEF patients has not been established since no randomized controlled trials (RCTs) were conducted exclusively on this population.…”
Section: Sex-related Difference In the Association Of Lower Lvef With...mentioning
confidence: 99%
“…Overall, 3498 unique records were identified from the search. Four reviews were hand-searched [11,[25][26][27]. No title or abstract was identified in a non-English language which would be considered for full-text review.…”
Section: Study Search and Selectionmentioning
confidence: 99%
“…As stated above, CR programmes are endorsed as part of the standard management strategy of IHD[ 4 , 6 , 7 , 75 ]. Whilst this, data has shown that CR is often underutilized and that even in those who are referred for this intervention, many do not complete the pre-specified programme[ 8 , 13 , 14 , 77 , 78 ]. Notably, while the issue of CR underutilization can affect a substantial number of individuals, as illustrated by data from the ESC-EORP EUROASPIRE V study where less than half of individuals with CAD were referred for CR, this can particularly affect certain subgroups such as women and older patients[ 77 - 81 ].…”
Section: Challenges To Crmentioning
confidence: 99%